Evaluation of Critical Success Factors in The Indonesian Automotive Industry using DEMATEL-Based ANP to Implement Green Supply Chain Management - Rivero, Max Dewar; Ardi, Romadhani (Universitas Al Azhar Indonesia, 2025)
Analysis of Indonesian car production data in 2022 shows significant trend for increase in production and sales from year to year. The automotive industry in Indonesia is currently an important non-oil and gas sector which has a major contribution to the national economy. Currently, Indonesia has 22 four-wheeled motor vehicle industry companies. The higher the level of car production, the higher the CO2 emissions produced, and the higher the worldwide pressure to the countries to reduce the CO2 emission damage. Therefore car companies must implement Green Supply Chain Management (GSCM). However, the many criteria in GSGM implementation make it difficult for industry players to decide on the appropriate strategic decisions. The aim of this study is to find out the critical success factors in implementing GSCM in the Indonesian automotive industry and their interrelationship. The method used in this study is the Decision Making Trial and Evaluation Laboratory (DEMATEL) based on the Analytic Network Process (ANP). The results of this study show that the top five of 25 critical success factor in global weight are: top management perspective 4.86%, company competitiveness 4.57%, economic interest 4.55%, Using energy-efficient machinery and equipment 4.49% and Carbon footprint identification 4.48%.Keywords - Automotive Industry, Critical Success Factors, DEMATEL Based ANP, Green Supply Chain Management.